2012
DOI: 10.1002/maco.201206654
|View full text |Cite
|
Sign up to set email alerts
|

Ternary mixes with high mineral additions contents and corrosion related properties

Abstract: The choice of blended cements and materials with cementitious properties in concrete is currently seen as a choice that increases the environmental sustainability of the construction industry. The developments with non‐traditional binders (such as the simultaneous incorporation of several types of supplementary cementitious materials) have highlighted new challenges to be researched. In the present paper ternary binders were prepared by mixing ordinary Portland cement (OPC) plus two blended components: low cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 33 publications
4
12
0
Order By: Relevance
“…As similarly reported in earlier studies [5][6][7]15], the ternary blended concrete specimens showed considerably lower mechanical properties at early ages (see Fig. 5) compared to OPC since it was still too early for the high portions of mineral admixtures (i.e., fly ash and GGBFS) to produce significant degrees of pozzolanic reactions for strength increase.…”
Section: Testing Results Of the Concrete Mixtures Of Opc 4-4-2 And supporting
confidence: 69%
See 1 more Smart Citation
“…As similarly reported in earlier studies [5][6][7]15], the ternary blended concrete specimens showed considerably lower mechanical properties at early ages (see Fig. 5) compared to OPC since it was still too early for the high portions of mineral admixtures (i.e., fly ash and GGBFS) to produce significant degrees of pozzolanic reactions for strength increase.…”
Section: Testing Results Of the Concrete Mixtures Of Opc 4-4-2 And supporting
confidence: 69%
“…Because the vast use of industrial by-products such as ground granulated blast furnace slag (GGBFS) and coal-fired fly ash (fly ash) enable significant cost savings for concrete production as well as lead to a more ecologically sustainable society, GGBFS and fly ash are commonly incorporated into Portland cement (cement) concrete mixtures in South Korea. In particular, the most important technical benefit is the reduction of thermal cracking due to the lower heat generation of the cement hydration than the use of only Portland cement for concrete production [2][3][4][5][6]; thus, there have been extensive attempts to increase the ratio of GGBFS and fly ash in the cement concrete mixtures in South Korea. However, most previous studies have investigated relatively low replacement ratios of the industrial by-products between 20% and 50% in concrete production and only a few studies examined higher substitution ratios over 60% [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…This effect is more relevant when additions with different hydration mechanism are combined (11,15,(17)(18)(19)(20)(21)(22)(23). The future of CEN (European Committee for Standardization) is on the way to include the ternary blends in the standards (9).…”
Section: Introductionmentioning
confidence: 99%
“…Different studies showed that ternary blends using PC with relatively high alkali and C 3 A content had lower initial mechanical strength than plain PC (5,18,19,22,24), while in mixes with PC containing low alkali and/or C 3 A content this effect is less relevant (11,15,20,21,23,25). Dehuai and Zhaoyuan (24) found that in ternary blends composed of 50-70% PC with 8% C 3 A and 0.9% Na 2 O eq .…”
Section: Introductionmentioning
confidence: 99%
“…The behaviour of steel embedded in blended cement is not so well known. The electrochemical study of corrosion resistance in ternary mixes (incorporating slag and fly ash) indicates that a passive state is reached and even suggests a lower corrosion rate after passivation compared to Ordinary Portland Cement mortar [11]. In contrast, the electrochemical impedance spectrometry (EIS) response of steel electrodes immersed in synthetic pore solution of a blast furnace slag cement (CEM III type, according to European standards) presents an active behaviour at 5 days [12].…”
Section: Introductionmentioning
confidence: 99%